Dakwah Moderasi di Tengah Pandemi Covid 19 - Muhamad Bisri Mustofa, Siti Wuryan (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
Moderation is an effort to give someone freedom in expressing all aspects of their lives, by promoting the foundation of tolerance, unity, togetherness, diversity, sincerity, honesty, and middle ground (wasathiyah). Da'wah in its context has a close relationship with moderation, because in Da'wah also known as the 3 methods of Da'wah approach namely: bil hikmah, mauidzoh hasanah, and mujadalah. Bil wisdom (wise) puts forward wise things, can put things with full justice this principle in line with moderation. Then mauidzoh hasanah (in a better way), every behavior takes precedence through a better way, and finally is mujadalah (discussing) this indicates that everything needs to be found a way out by prioritizing deliberation and musfakat, especially in carrying out preaching. Apart from all aspects of the da'wah method and substance of moderation, the covid 19 pandemic caused a new chapter in the da'wah moderation, by carrying out physical distancing, clean living, and wearing masks. Da'wah moderation is implemented through online technology (in the network) that can access all the mad'u through applications such as Zoom Cloud Meeting, Google Meeting, Webbex, Skype, and others.